The Effect of Green Supply Chain Management, Green Intellectual Capital, and Green Information System on Environmental Performance and Financial Performance - Renaldo, Nicholas; Augustine, Yvonne (Archives of Business Research, 2022)
Environmental degradation is increasing and resource depletion has become a problem. Based on the results of the preliminary survey, the majority of respondents are more concerned with financial performance than environmental performance. This study aims to examine the effect of green supply chain management (GSCM), green intellectual capital (GIC), and green information system (GIS) on environmental performance (EnvP) and financial performance (FinP). The sample in this study was 219 respondents who came from manufacturing companies in Riau Province. Data analysis used structural equation analysis with SMART PLS application. The results show that only green supply chain management has a positive effect on financial performance. Then green intellectual capital and environmental performance each have a positive effect on financial performance. This research develops a new measurement for green supply chain management and green information system variables. Companies can develop systems and information technology that can reduce waste so that their environmental and financial performance can be better.